Endoscopic visualization of cancer and dysplasia in patients with ulcerative colitis following sensitization with oral 5‐aminolevulinic acid. Issue 9 (28th September 2020) - Kato, Tomohiro; Iwasaki, Tetsuyoshi; Arihiro, Seiji; Saruta, Masayuki
Abstract : Objective: Early diagnosis of colitis‐associated cancer and dysplasia through surveillance endoscopy is vital for patients with ulcerative colitis (UC). This study aimed to evaluate the efficacy of autofluorescence endoscopy (AFE) using 5‐aminolevulinic acid (ALA) and to investigate the fluorescence signal localization pattern following 5‐ALA administration in tumorous lesions diagnosed as colitis‐associated cancer and dysplasia. The sensitivity and specificity of tumorous lesions detected by white light endoscopy (WLE) with and without AFE were evaluated. Methods: Overall, 13 endoscopic procedures were performed in 11 patients with UC using WLE and AFE following the oral administration of 5‐ALA. The biopsied lesions detected via endoscopy and resected specimens from cases underwent colectomy were assessed histopathologically. The sensitivity and specificity of detecting tumorous lesions by WLE with and without AFE were evaluated. Results: Of the 68 lesions detected and biopsied, 63 were detected via WLE, and five were detected via AFE alone. The sensitivity of detecting colitis‐associated cancer and dysplasia via WLE combined with AFE was 36.4%, and the specificity, positive predictive value and negative predictive value were 94.2%, 57.1%, and 87.5%, respectively. Tumorous lesions displayed three types of fluorescence patterns on AFE. Conclusions: AFE using 5‐ALA can detect colitis‐associated cancer and dysplasia in patients with long‐standing UC and lesions that could not be detected via WLE. The distinctive fluorescence patterns in lesions may permit qualitative diagnoses of colitis‐associated cancer and dysplasia.